THE EFFECT OF USING FERMENTEDWATER SPINACH LEAVES (Ipomoea aquatica,Forsk.)IN DIET ON GROWTH OF GOURAMY (Osphronemus gouramy)FINGERLING - Herlita Noveni Samosir; Adelina Adelina; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The research was conducted in September-November 2018. The aim of the research was of determine the percentage of usage fermented water spinach leaves (FWSL) flour in gouramy feed to produse feed efficiency and growth of gouramy seeds.  The research uses a competely randomized design (CRD) with one factor 5 treatment and 3 replications. The treatment in this research was the use of fermented water spinach leaves meal in diet different percentage namelyP0(0%FWSL), P1(20%FWSL), P2(30%FWSL), P3(40%FWSL) and P4(50%FWSL) in feed.  The results showed that the best treatment was found in P3 which was produced 74,8%feed digertibility,31,5% spesific growth rate and 41,83%feed efficiencyof gouramifingerling. Keyword:Artifical feed, Fermentation, Gouramy, Water Spinach Leaves.